Religion and Covid-19 in the era of post-truth: the case of Indonesia - Widiyanto, Asfa (Penerbit Universiti Kebangsaan Malaysia, 2020)
Coronavirus disease (Covid-19) has become global pandemic, which affects all countries in the world including Indonesia. The mitigation of covid-19 pandemic in Indonesia cannot neglect the role of religion, since religion constitutes the main identity of most people. Hence, religion becomes value reference and ‘system of knowing’, including in addressing the covid-19 pandemic. By employing comparative and content analysis, it is hoped that this paper will constitute a significant contribution in unravelling the complex role of religion in dealing with covid-19 pandemic, most particularly in the context of post-truth. There are three concerns of this paper. First, it examines the challenges of religious conservatism towards covid-19 mitigation among Indonesian Muslims, most particularly in the context of post-truth which in some ways intensifies the emergence of conservativism in the public space. Second, it explores the possibility of ‘new spirituality’ which is pertinent for the mitigation of Covid-19. Third, it explores the contribution of Indonesian Muslim knowledge culture to the fight against covid-19.